PKM OPTIMALISASI SKALABILITAS PRODUKSI DAN INOVASI MANAJEMEN UNTUK MENINGKATKAN USAHA NAZ CAKE AND COOKIES LAMPUNG - Dewi, Fajar Gustiawaty; Alvia, Liza; Agramanisty Azdy, Rezania; Novelidhawaty, Yossie (LPPM Universitas Bina Bangsa, 2025)
Naz Cake & Cookies is a small and medium-sized enterprise (SME) engaged in the food industry, specializing in various cakes, traditional snacks, and bread. The production site is located in Perum Beringin, Kemiling District, Bandar Lampung, approximately 7 km from the University of Lampung. This business was founded by M. Fa’iq Teza Putra on January 27, 2009, and obtained its Business Identification Number (NIB) on February 3, 2021, while also being a registered taxpayer.Several challenges faced by the partner include: difficulties in financial management, ineffective financial record-keeping, suboptimal stock management, disorganized storage and poor maintenance of production equipment, and an ineffective First In First Out (FIFO) system.To address these issues, the Program Implementation Team has proposed solutions, such as improving business and production management by applying Appropriate Technology (TTG), including the Naz e-inventory system and si APIK Application training from Bank Indonesia. The program runs for eight months through several stages, including situation analysis, training, and evaluation. The program outcomes include several publications, video tutorials, promotional designs, the provision of production tools, and results indicating an increase in partner knowledge and skills by up to 90% in business management, 87% in production, and 85% in technology application